Strategies for eating and body change among Brazilian women and men - Da Silva, Wanderson R. [UNESP]; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (FapUNIFESP (SciELO), 2020)
Objectives: Our study was conducted to adapt the Body Image and Body Change Inventory (BIBCI) for Portuguese; to evaluate the BIBCI’s psychometric properties in samples of university students; to calculate the prevalence of strategies for eating and body change among students; and to evaluate the impact of demographic, social, and anthropometric characteristics on the BIBCI subscales. Methods: 798 students (women = 63%) answered the Portuguese translation of the BIBCI and answered a demographic questionnaire. All analyses were performed separately for women and men. The BIBCI’s psychometric properties were estimated using confirmatory factor analysis. Mean scores were calculated for each BIBCI subscale. A multivariate regression model was tested to evaluate the impact of demographic, social, and anthropometric characteristics on mean BIBCI subscale scores. Results: The psychometric properties of the BIBCI were adequate in the samples analyzed. The BIBCI subscales scores did not differ according to sex. According to the cut-off points adopted, most of the students were classified in the very low category of the BIBCI subscales. For women, characteristics such as self-reported eating assessment, economic class, physical activity level, and work were significant. For men, only physical activity level was significant. Conclusion: The Portuguese translation of the BIBCI was presented and its psychometric properties were found to be adequate in the samples analyzed. The models identified significant characteristics that can be used in intervention protocols for preventing inappropriate behaviors in relation to body image and eating.
Keywords: Body image; Eating; Men; Women